2009
DOI: 10.1039/b810895a
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectroscopy and molecular modelling studies of nitrosylcobalamin: further evidence that the deprotonated, base-off form is important for nitrosylcobalamin in solution

Abstract: The structure of nitrosylcobalamin (NOCbl) in solution has been studied by NMR spectroscopy and the 1 H and 13 C NMR spectra have been assigned. 13 C and 31 P NMR chemical shifts, the UV-vis spectrum of NOCbl and the observed pK base-off value of ~5.1 for NOCbl provide evidence that a significant fraction of NOCbl is present in the base-off, 5,6-dimethylbenzimidazole (DMB) deprotonated, form in solution. NOE-restrained molecular mechanics modelling of base-on NOCbl gave annealed structures with minor conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 74 publications
3
38
0
Order By: Relevance
“…Very recently, Brasch et al have shown that extension of this correlation to a larger number of cobalamins having distances with e.s.d. 's up to 0.01 Å, gave an R 2 value of 0.84 [39,40,43]. However, when the correlation is limited to Co\NB3 distances with e.s.d.…”
Section: Co-c (å)mentioning
confidence: 88%
See 3 more Smart Citations
“…Very recently, Brasch et al have shown that extension of this correlation to a larger number of cobalamins having distances with e.s.d. 's up to 0.01 Å, gave an R 2 value of 0.84 [39,40,43]. However, when the correlation is limited to Co\NB3 distances with e.s.d.…”
Section: Co-c (å)mentioning
confidence: 88%
“…The fast exchange between the base-on and base-off forms of NOCbl on the NMR time scale explains why the NOCbl signal does not fit the regression line. In alkylcobalamins [43] there is significantly less base-off form, which essentially does not affect the 31 P NMR signal, as for all the other inorganic cobalamins (from H 2 OCbl + to SO 3 Cbl − ), which are in base-on form, without appreciable presence of the base-off form.…”
Section: Co-c (å)mentioning
confidence: 93%
See 2 more Smart Citations
“…The Co-N α axial bond length to the DMB ligand of NOCbl is greater by 0.13 Å than the distance in the related NO 2 Cbl structure, reflecting the trans-labilizing effect of NO À . Both the axial "base-off" and "base-on" complexes coexist in aqueous solution at mild acidities, with predominance of the latter (deprotonated) form at pHs !7 (163). In an important application of the properties of Co(II)(por)/ Co(III)(por) fragments toward nitrosyl/nitroxyl coordination, a novel amperometric method has been developed, based on the attachment of a Co(II)(por) to a gold electrode and further electrochemical oxidation to Co(III).…”
Section: No 2 -Complexesmentioning
confidence: 99%